Validity and Reliability of Adult ADHD Self-Report Scale Persian Version (ASRS-V1.1-Persian): Adult ADHD Self-Report Scale Persian Version - Mousavi 1, Seyed Abbas; Bazrafshan 2, Zahra; Khosravi 3*, Ahmad (Shahroud Journal of Medical Sciences, 2020)
Background: Attention-deficit/hyperactivity disorder (ADHD) is a common mental disorder in adults. The objective of this study was to develop a valid Persian version of the 18-question ASRS-V1.1 according to WHO translation protocol and report its psychometric properties.Methods: In the first step, we translated the original 18-question ASRS-V1.1 version into Persian under the supervision of the WMH-CIDI advisory committee. The process of adaptation was consisting of forward-translation, expert panel evaluation, back translation, cross-cultural adaptation, pre-testing, and final adjustment. In the second step, we conducted a cross-sectional study with 734 students were studied in Shahroud in 2013. A sub-sample of subjects consists of 99 students were clinically interviewed according to DSM-IV-TR criteria by a well-trained physician.Results: The ASRS-V1.1-P had satisfactory internal consistency (Cronbach’s alpha = 0.85). Sensitivity and specificity for the first six questions of ASRS-V1.1-P were 50.0% (95% CI: 30.3-69.6) and 80.5% (95%CI: 70.7-88.3), respectively. Finally, 43 subjects (5.5%) were confirmed for adult ADHD. There was not sex predominance in the prevalence of ADHD.Conclusion: Totally, it may be concluded that adult ADHD is a common problem among students and prevention of this disorder is crucial to reduce the probable subsequent social, educational, and job problems in future. The 18-question ASRS-V1.1-P is a psychometrically reliable and valid measure for screening ADHD in adults. Keywords: Attention-deficit/hyperactivity disorder, Screening, Adult, Validity.